Analisis Topik dan Aktor pada Diskusi GeNose C19 - Andi Budiansyah; Mardhani Riasetiawan; Achmad Djunaedi; Ilmi Afrizal Rachim (Departemen Ilmu Komunikasi FISIP Universitas Atma Jaya Yogyakarta, 2024)
The GeNose C19 has rised a discussion on Twitter. This study seeks to analyze and categorize topics and actors who have a significant role in spreading knowledge on the usage of GeNose C19 on Twitter between March 1st, 2020, and December 20th, 2021. The findings of this study include various topic, namely pertaining to its mechanisms and operations, superiority, marketing approval, user experience, and product comparison. Actors who played a significant role in spreading knowledge were players from the media, colleges, and government. In addition, state-owned companies play an important part in distributing technical knowledge to the public.